Blue Cap Relay Run for Prostate Cancer® - Sothilingam, S.; Razack, A.H.A.; Lim, J. (University of Malaya, 2016)
The Blue Cap Relay Run for Prostate Cancer aims to raise awareness of men's health & prostate cancer and encourage cancer patients leading a healthy lifestyle after treatment. This 3 x 3 km relay run, which organized by the Blue Cap Movement, is a brand new relay run concept involving cancer survivors. There are 3 members in a team in which each member would need to complete a 3 km run. Six categories are available in the relay run and one of them is exclusive for cancer survivors running with their family members or friends. All funding raised will be utilized in support of prostate cancer treatment. This trademark registered under class 25, 36, 41 and 45.